Prevalence and antibiogram of Shigella and Salmonella spp. from under five children with acute diarrhea in Bahir Dar Town - Admassu, Maritu; Yemane, Gebremariam; Kibret, Mulugeta; Abera, Bayeh; Nibret, Endalkachew; Adal, Melaku (Ethiopian Journal of Science and Technology, 2025)
Diarrheal diseases remain the major cause of morbidity and mortality in children under five years of age. Salmonella and Shigella species are among the leading causes of diarrhea in children. The aim of this study was to determine the prevalence and antimicrobial profiles of Salmonella and Shigella spp. in children less than five years of age with acute diarrhea. A cross sectional study was conducted among 422 children with diarrhea from December 2011 to February 2012. A structured questionnaire was used to collect socio-demographic and clinical data. Identification of Salmonella and Shigella species and antimicrobial susceptibility tests was done following standard microbiology procedures. The overall prevalence of Salmonella and Shigella was 7.8% and 9.5 %, respectively. The isolation rates of S. flexineri, S.dysenteri and S. boydii were 18 (45 %), 12 (30 %) and10 (25 %), respectively. The prevalence of Salmonella and Shigella were not statistically significant along age groups and gender of the children. Most of Salmonella and Shigella were resistant to ampicillin (> 88.7%) and cotrimoxazole (50%).In contrast, 83.3-89.9% of isolates showed susceptible to norfloxacin, ciprofloxacin and gentamicin. More than 90% of the Salmonella and 80% Shigella spp. were multiple drug resistant. High prevalence of Shigella and Salmonella linked with high levels of antimicrobial resistance is a major public health concern in the study area. Continuous surveillance of antimicrobial susceptibility should be done. Ciprofloxacin, norfloxacin and gentamicin appeared to be drugs of choice for empirical treatment of these infections.